2017
DOI: 10.1097/md.0000000000006713
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for detection of the primary tumor in adults with extracervical metastases from cancer of unknown primary

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 29 publications
4
38
0
3
Order By: Relevance
“…[ 18 F]-2 deoxyglucose ( 18 F-FDG) is a conventional clinical PET imaging agent, which is mainly based on the higher metabolism and more uptake of glucose of tumor tissues than normal tissues. 17,18 However, as a nonspecific tumor imaging agent, 18 F-FDG is highly biased for early diagnosis of lung cancer because of the slow growth and reduced glucose metabolism of early lung cancer. 19 In addition, inflammatory sites can also accumulate high concentrations of 18 F-FDG imaging agent, resulting in misdiagnosis of clinical lung cancer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 18 F]-2 deoxyglucose ( 18 F-FDG) is a conventional clinical PET imaging agent, which is mainly based on the higher metabolism and more uptake of glucose of tumor tissues than normal tissues. 17,18 However, as a nonspecific tumor imaging agent, 18 F-FDG is highly biased for early diagnosis of lung cancer because of the slow growth and reduced glucose metabolism of early lung cancer. 19 In addition, inflammatory sites can also accumulate high concentrations of 18 F-FDG imaging agent, resulting in misdiagnosis of clinical lung cancer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…CT scans of thorax, abdomen and pelvis constitute a minimal basic workup . PET/CT scan has rapidly become the new standard imaging in the abdomen/pelvis and is characterized by high detection rate of a primary tumour in CUP but the guidelines limit its role to cervical CUP and single CUP metastasis . The role of PET/CT scan should be reconsidered in prospective studies in view of its positive input in anogenital tumours .…”
Section: Discussionmentioning
confidence: 99%
“…1 PET/CT scan has rapidly become the new standard imaging in the abdomen/pelvis and is characterized by high detection rate of a primary tumour in CUP but the guidelines limit its role to cervical CUP and single CUP metastasis. 1,25,26 The role of PET/CT scan should be reconsidered in prospective studies in view of its positive input in anogenital tumours. 27,28 Nevertheless, its effectiveness may be limited by the low metastatic potential of this CUP subset as only 12.5% of patients presented distant metastasis.…”
Section: Perspectivementioning
confidence: 99%
“…[ 3 ] Previous literature has shown that the role of FDG-PET is limited, with a primary lesion detection rate of approximately 40% in patients with CUP. [ 4 ] Examinations of biopsy specimens are mandatory, and immunohistochemistry is the gold standard for diagnosing CUP. [ 5 ] Keratin expression patterns of the biopsy specimen of this patient were consistent with the diagnosis of epithelial tumor, such as lung adenocarcinoma, breast ductal carcinoma, ovarian serous papillary carcinoma, and endometrial adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%